Computer Simulations of Direct Imaging of Extrasolar Planets - Jallod, Uday; Mohammed, A. (Iraqi Journal of Science, 2024)
Numerical simulations are carried out to investigate the possibility of observingextrasolar planet nearby star via optical telescopes. Several techniques areconsidered in this study in order to quantitatively assess their quality in suppressingthe wings of the point spread function of optical telescope of a reference star. Theoptical telescope with circular Gaussian shape aperture reveals extrasolar planeteven with contrast ratio 10-7 while the square Gaussian shape aperture reveals theplanet with 10-5.